Numerical Constraints on Folding and Thrusting in Jiudong Basin: Implication for the Northeastward Growth of Qinghai–Tibetan Plateau - Chen, Qizhi; Hu, Caibo; Orellana-Rovirosa, Felipe; Zhou, Longshou; Zhang, Huai; Shi, Yaolin (Frontiers in Earth Science, 2022)
Under regional tectonic shortening in the northern margin of Qinghai–Tibetan Plateau, the fold-and-thrust belts composed of four thrust faults (North Qilian-Shan, North Yumu-Shan, South Heli-Shan, and North Jintanan-Shan) formed from southwest to northeast discontinuously sequentially in the Jiudong Basin area during Late Cenozoic. Meanwhile, the North Qilian-Shan, Yumu-Shan, and Heli-Shan ranges were formed successively, as the Earth's local surface was unequally uplifted. In this study, based on geological and geophysical observations, a simple two-dimensional elastic-plastic numerical finite element method model for a southwest-northeast section in Jiudong Basin is successfully established to simulate the spatiotemporal evolution of the local fold-and-thrust belts. Results show that the computed equivalent plastic strain concentration zones and the four observed thrust faults are consistently correlated in spatial position orientation and time sequence. The simulated upper-surface deformation is congruent with the observed topographic peaks and uplift sequences of the North Qilian-Shan, Yumu-Shan, and Heli-Shan ranges. This study provides a geodynamic basis for understanding the growth mechanism of the northern margin of Qinghai–Tibetan Plateau under tectonic horizontal shortening. Also, we provide a thorough sensitivity analysis for the model parameters of this particular geologic setting. Our sensitivity simulations, considering systematic case variations about the regional geometrical-material parameters, suggest the manifestation of three different possible evolution patterns of fold-and-thrust belts for a wedge above a decollement layer, with wedge plastic deformation migrating from 1) thick to thin end (well-known), 2) thin to thick end, and 3) both ends to middle. Finally, our results suggest that in this region, further growth of mountain ranges is expected to continue in the future.